2020
DOI: 10.3390/s20020466
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Response to Transient Redox Stress in Human Isolated T Cells: Molecular Sensor Role of Syk Kinase and Functional Involvement of IL2 Receptor and L-Selectine

Abstract: Reactive oxygen species (ROS) are central effectors of inflammation and play a key role in cell signaling. Previous reports have described an association between oxidative events and the modulation of innate immunity. However, the role of redox signaling in adaptive immunity is still not well understood. This work is based on a novel investigation of diamide, a specific oxidant of sulfhydryl groups, and it is the first performed in purified T cell tyrosine phosphorylation signaling. Our data show that ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The results shown represent only a limited portion of the potential of the proposed model which, nevertheless, needs specific experimental validation for demonstrating its full reliability and effective applicability. Work is underway to include for example the effect of cell cycle synchronization factors (Banfalvi, 2017;Pantaleo et al, 2017;Secchi et al, 2020). This aspect is of peculiar importance for infection with lentivirus (Trobridge and Russell, 2004;Bonfalvi, 2017;Pantaleo et al, 2017;Secchi et al, 2020) to generate GM cells, typically for mAb production (or any other recombinant protein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shown represent only a limited portion of the potential of the proposed model which, nevertheless, needs specific experimental validation for demonstrating its full reliability and effective applicability. Work is underway to include for example the effect of cell cycle synchronization factors (Banfalvi, 2017;Pantaleo et al, 2017;Secchi et al, 2020). This aspect is of peculiar importance for infection with lentivirus (Trobridge and Russell, 2004;Bonfalvi, 2017;Pantaleo et al, 2017;Secchi et al, 2020) to generate GM cells, typically for mAb production (or any other recombinant protein).…”
Section: Discussionmentioning
confidence: 99%
“…Work is underway to include for example the effect of cell cycle synchronization factors (Banfalvi, 2017;Pantaleo et al, 2017;Secchi et al, 2020). This aspect is of peculiar importance for infection with lentivirus (Trobridge and Russell, 2004;Bonfalvi, 2017;Pantaleo et al, 2017;Secchi et al, 2020) to generate GM cells, typically for mAb production (or any other recombinant protein).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the absence of CD25 in peripheral Tregs was determinant of their increased susceptibility to oxidative stress, mitochondrial dysfunction, and apoptosis and of the transcription of lipid and cholesterol biosynthetic key enzymes ( Toomer et al, 2019 ). Moreover, CD25 expression at the cell surface was dependent on a redox-regulated signaling pathway ( Secchi et al, 2020 ) and was decreased on Tregs from aged mice ( Chougnet et al, 2011 ). Taking all these data into account, since older KO-T PPARβ/δ mice display less FoxP3 + CD25 – cells (accompanied by a concomitant increase in FoxP3 + CD25 + cell proportion), one might expect that Tregs of these mice are preserved from the effects of aging and oxidative stress, and thus more functional and less prone to immunosenescence.…”
Section: Discussionmentioning
confidence: 99%
“…From a structural perspective, as noted by Go and Jones, thiol redox modifications can be classified into four different types of switches that have a modulatory effect: on-off (protein in-/activation), interaction (binding), allosteric (regulates activity), and thiolation (alternate function) [ 44 ]. As some thiol-based redox modifications are reversible, this can permit rapid activation or inactivation of signaling pathways [ 45 ], leading to their transient activity [ 46 , 47 ]. One example is the transient receptor potential (TRP) family of Ca 2+ cation channels that are found in photoreceptors and other cell types.…”
Section: Introductionmentioning
confidence: 99%